1999
DOI: 10.1007/bf03012550
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptanesthesia: current status

Abstract: FRCPCPurpose: To review the current status and possible future of neuroleptanalgesia/anesthesia, techniques that may be nearly extinct. Souzce: Articles from 1966 to present were obtained from the Current Science and Medline databases. Search terms include neurolepananalgesia/anesthesia, conscious sedation, droperidol, benzodiazepines, propofol, ketamine, and opioids. Information and abstracts obtained from meetings on this topic helped complete the collection of information. Principal findings: Droperidol/fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…Although high doses of propofol are required to produce EEG suppression, opiates usually combined with a hypnotic allow a propofol-sparing effect. High-dose infusion of sole fentanyl results in slowing of EEG progressing to the formation of delta waves (4 Hz, amplitude 50 mV) but does not produce EEG burst suppression [9]. A supraadditive interaction between fentanyl and propofol has been reported for clinical signs such as loss of consciousness, loss of the eyelash reflex, or regaining consciousness as well as EEG changes [10,11].…”
Section: Discussionmentioning
confidence: 98%
“…Although high doses of propofol are required to produce EEG suppression, opiates usually combined with a hypnotic allow a propofol-sparing effect. High-dose infusion of sole fentanyl results in slowing of EEG progressing to the formation of delta waves (4 Hz, amplitude 50 mV) but does not produce EEG burst suppression [9]. A supraadditive interaction between fentanyl and propofol has been reported for clinical signs such as loss of consciousness, loss of the eyelash reflex, or regaining consciousness as well as EEG changes [10,11].…”
Section: Discussionmentioning
confidence: 98%
“…However, the mechanisms by which droperidol elicits this morphine-sparing effect are not clear currently [9]. Droperidol has previously been used as a premedicant before the induction of general anesthesia or, alternatively, in combination with various opioids to facilitate induction of anesthesia and potentiate opioid analgesic activity [10]. Chien and Pasternak [11] reported that combination with haloperidol, an analogue of droperidol, increases the level of morphine analgesia by 60% or more, with the increased analgesic activity mediated through blockade of the sigma receptors.…”
Section: Discussionmentioning
confidence: 98%
“…Complications of neuroleptanaesthesia include muscle rigidity, postoperative extrapyramidal excitation and excessive sedation. 21 …”
Section: Neuroleptanaesthesiamentioning
confidence: 97%